The impact of charge transfer inefficiency on Extreme Precision Doppler measurements. (3rd April 2017) - Blake, C.H.; Halverson, S.; Roy, A.
Abstract: A new generation of ``Extreme Precision'' astronomical spectrometers is currently being designed to detect Earth-mass planets orbiting nearby stars using the Doppler method. Measuring the subtle shifts in stellar absorption features resulting from stellar radial velocity variations of tens of centimeters per second is a significant technological challenge. Currently, there are several instruments around the world capable of measuring stellar radial velocities at the 1 m s −1 level. Moving beyond this level of precision, CCD effects may become important and could limit the ultimate measurement precision in complex ways. Here, we simulate the impact of Charge Transfer Inefficiency (CTI) in CCDs on radial velocity measurements. We show that CTI can manifest as a significant source of systematic error in high precision Doppler measurements, though these effects can likely be mitigated using optimized observing strategies and empirical flux corrections.